Attitudes of the Elite Groups towards the ultra-poor: secondary stakeholders in the CFPR-TUP - Chowdhury, Manosh; Lapenna, Lily; Mishu, Abu Ahasan (BRAC Research and Evaluation Division (RED), 2019)
"Attitudes of the Elite Groups towards the Ultra-Poor Secondary stakeholders in the CFPR-TUP" was initiated as a combined effort between Advocacy and RED. Secondary stakeholders are those that beyond the primary stakeholders have the potentials to contribute to the success of implementing and running the CFPR/TUP program, by having a crucial impetus in the design of the participatory process. The purpose of the research is to analyze and suggest which stockholders can effectively contribute and how. Secondary stakeholders range from administration officials, civil servants to NGO workers. Program recognizes that it cannot help reduce the vulnerabilities and expand the opportunities of the poor, especially women, without redressing unbalanced power relationships and oppressive social practices. For this reason, program seeks to promote what it calls the socio-political assets - not just social assets - of the poor. The elite people are not. in general, willing to have a regular social bondage with the ultra-poor people. Either they are ignorant of, or reluctant to the situations of the ultra-poor. Socially they do maintain a huge distance. Only exception is the rural landowners and the persons in the GSCs. The development programs generally are accepted among the elite people. Major areas of elite people's interest are education and housing, the areas favored already by the NGOs. But small-scale income generating programs are also a asserted priority of the elite people.